Media Pembelajaran Tutorial Akupressure Facial Meningkatkan Hasil Belajar Mahasiswa Mata Kuliah Perawatan Wajah Konsentrasi Tata Rias - Izmi Burhanuddin; Rosmiaty Rosmiaty; Syamsidah Syamsidah (Universitas Negeri Makassar, 2022)
This study aims to determine the process of developing learning media using effective and practical video tutorials and to improve student learning outcomes. This research is a development research that is focused on developing learning media in the Face Care course. This study uses a development model that refers to the ADDIE development model which is carried out in five phases, namely: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation (evaluation). Based on the research, it can be concluded as follows: (1) the tutorial media development procedure uses the ADDIE development model; (2) instructional media video tutorials, effective, and practical with good categories, (3) learning media video tutorials seen from the implementation of learning, the results of observations of lecturers and students, as well as the results of the analysis of pre-test and post-test an increase in order to achieve the criteria of effectiveness and practical so that it can improve student achievement in the PKK Department of Cosmetology Concentration FT UNM.